Corporate Profit Growth as a Result of Fluctuations in Activity Ratio, Solvency and Liquidity - Edwin Agus Buniarto; Dian Ferriswara; Amirullah Amirullah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines the impact of financial performance indicators—activity, solvency, and liquidity ratios—on profit growth in pulp and paper manufacturing companies listed on the Indonesian Stock Exchange from 2019 to 2024. The research focuses on how variations in Total Assets Turnover, Inventory Turnover, Fixed Assets Turnover, Debt to Equity Ratio, and Quick Ratio affect profitability, especially during periods of economic instability like the COVID-19 pandemic. The aim is to identify which financial ratios have the most significant influence on profit performance. A quantitative research method was employed, utilizing secondary data from 42 observations of seven manufacturing firms, selected through purposive sampling. Multiple linear regression analysis, supported by SPSS software, was used to test the hypotheses. The findings show that all five ratios collectively have a significant impact on profit variations, with an F-statistic of 2.568 and a significance value of 0.044. However, when tested individually, only Total Assets Turnover and Inventory Turnover showed significant effects, while Fixed Assets Turnover, Debt to Equity Ratio, and Quick Ratio did not. The coefficient of determination (R²) was 0.263, indicating that 26.3% of the variation in profit can be explained by the analyzed variables.